An efficient one-pot synthesis of tetra-substituted pyrroles - Ghabraie, Elmira; Balalaie, Saeed; Bararjanian, Morteza; Bijanzadeh, Hamid Reza; Rominger, Frank (Tetrahedron, 2011)
The three-component reaction of primary amines, dialkyl acetylenedicarboxylates and β-nitrostyrene derivatives in the presence of Iron(III) chloride afforded 1,2,3,4-tetra-substituted pyrroles in high yields. These reactions could precede via domino Michael addition/cyclization process.